Procalcitonin as a diagnostic tool for bacterial neonatal sepsis - Nely Nelly; Guslihan Dasa Tjipta; Hakimi Hakimi; Bugis Mardina Lubis (Indonesian Pediatric Society, 2015)
Background Bacterial sepsis is the main cause of morbidity and mortality in neonates. Early diagnosis and appropriate treatment can reduce the mortality rate. Blood culture is the gold standard for diagnosis of bacterial sepsis, but it requires 3-5 days for results. Since the disease may progress rapidly in neonates, a faster diagnostic test is needed. Measurement of procalcitonin levels may be a quick method to diagnose bacterial sepsis in neonates. Some studies found the sensitivity of procalcitonin to be between 92-100%. Objective To assess the use of procalcitonin as an early diagnostic tool for bacterial neonatal sepsis. Methods This diagnostic study was conducted from October 2011 to February 2012. Forty-three neonates in the Perinatology Unit at H. Adam Malik Hospital were suspected to have bacterial sepsis. They underwent routine blood counts, blood cultures, as well as C-reactive protein and procalcitonin measurements. Subjects were collected by consecutive sampling. The gold standard of sepsis was based on any microorganism found in blood culture. Results Of 43 neonates, 36 neonates had bacterial sepsis. We found that procalcitonin sensitivity was 100%, specificity 85.71%, positive predictive value 97.29% and negative predictive value 100%. The ROC curve showed a cut-off point of 0.929 (95%CI 0.713 to 0.953). Conclusion Procalcitonin is useful as an early diagnostic tool for bacterial neonatal sepsis.